Mitochondrial abnormalities in oculopharyngeal muscular dystrophy - Wong, K.T.; Dick, D.; Anderson, J.E.R. (Faculty of Medicine, University of Malaya, 1996)
This report describes a 56-yr-old man with a dominantly inherited disorder affecting four generations and characterized by bilateral ptosis and dysphagia. Muscle biopsy showed only minor light microscopic abnormalities but electron microscopy revealed fibres containing paracrystalline mitochondrial inclusions. Southern analysis of mitochondrial DNA obtained from muscle did not reveal mitochondrial gene deletions. An extensive search eventually identified the characteristic intranuclear filaments of oculopharyngeal muscular dystrophy (OPMD). Abnormal mitochondria are non-specific epiphenomena in OPMD but a potential source of confusion with a late-onset mitochondrial cytopathy. This case further emphasizes the necessity for a diligent search for the diagnostic intranuclear filaments when oculopharyngeal muscular dystrophy is suspected clinically.